Characteristics of in situ synthesized activated carbon and metal‐organic framework composites for CH4/N2 gas mixture separation. Issue 1 (19th December 2022) - Zheng, Yuannan; Li, Qingzhao; Yu, Guofeng; Jiang, Bingyou; Ren, Bo; Wang, Shiju
Abstract: In this study, activated carbon and metal‐organic framework composites were synthesized by in situ hydrothermal method, and the surface morphology, physicochemical structure and adsorption performance of the materials were tested. Moreover, the competitive adsorption characteristics of CH4 /N2 gas mixture on the materials MIL‐101, DFAC‐MIL‐101 and NMAC‐MIL‐101 were predicted based on the ideal adsorption solution theory (IAST). Results show that the rod‐like fibers formed after doping with activated carbon did not affect the crystal structure of the metal‐organic framework material but caused the unevenness and passivation of the crystal surface, and the crystal size of MIL‐101 was significantly decreased due to which the micropores of the composite material were more developed, while the mesopores and macropores were decreased accordingly. Meanwhile, the micropore size of MIL‐101 and Ac‐MIL‐101 composite materials were mainly distributed around 0.9, 1.2 and 1.7 nm. The adsorption isotherms of these three materials for CH4 and N2 had typical type I characteristics, and the adsorption selectivity S for binary CH4 /N2 gas mixture is greater than 2. Doping activated carbon could properly control the structure of MIL‐101 crystals and improved the selectivity effectively, which provides a certain guiding significance for the structure regulation and application of MIL‐101 metal‐organic framework materials. © 2022 Society of Chemical Industry and John Wiley & Sons, Ltd.